Age of information foundations and applications - Pappas, Nikolaos 1982-; Abd-Elmagid, Mohamed A. ca. 20./21. Jh; Zhou, Bo; Saad, Walid ca. 20./21. Jh; Dhillon, Harpreet S. ca. 20./21. Jh (Cambridge University Press, 2023)
A comprehensive treatment of a crucial tool, this text provides detailed exposition of the communication and network theoretic foundations of Age of Information. It includes extensive real-world applications including caching, the Internet of Things, and energy harvesting networks, making this a vital resource for graduate students and researchers.
Includes bibliographical references and index
Keywords: Leistungsbewertung; Telekommunikationsnetz; Telecommunication